Factors influencing international students’ adoption of generative artificial intelligence: The mediating role of perceived values and attitudes - Ittefaq, Muhammad; Zain, Ali; Arif, Rauf; Ahmad, Taufiq; Khan, Laeeq; Seo, Hyunjin (Journal of International Students, 2025)
The present study examines the factors influencing international students’ intentions to use generative artificial intelligence (GenAI). Our results showed that attitude toward GenAI use, perceived ease of use, perceived usefulness, enjoyment, subjective norms, novelty, trust in technology, perceived value, and AI literacy were positively associated with intention to use GenAI. Fear of plagiarism had a negative relationship with intention to use GenAI. Our mediation analysis suggested that trust in technology, perceived ease of use, fear of plagiarism, perceived usefulness, and AI literacy indirectly influenced GenAI usage intention via attitude and perceived value, underscoring both the appeal and concerns of GenAI in learning. This study contributed to the TPB, VAM, and TAM frameworks by incorporating fear of plagiarism, trust in technology, and AI literacy to demonstrate how cognitive, affective, and value-based factors collectively influence the adoption of GenAI technologies among international students.